(3QSGdI aj GdaQb Hjf GdQhM hGdfaSs - (3YHO Gddg Hf GdWjH GdHZOGOj , nCoHh GdnanQL GHf GdpqWpqjH , J (B435 (3g` s
(3ChdgG (B:s
(3GdQhM LSe dWja ehLhO ai GdOeGZ hGdbdH hGdcHO s
(3BNQgG (B:s
(3QhM GdOeGZ CdWa ddWa aYdg hGdPi ai GdChSW hGdNdai CdWa ef GdPi ai GdebOe ddWa GdaYd , hGdMeO ddg TcQkG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B5s
(3fSNI fajSI LOkGs
(3eUOQ GbJfGA GdCUd (B:s
(3ESchQjGd (B(888/5) s
Keywords: (3GdadSaI hGdefWbs